2020
DOI: 10.1017/s0031182020001146
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of anthelmintics on Angiostrongylus cantonensis L3 larvae

Abstract: Angiostrongylus cantonensis is the leading cause of eosinophilic meningitis worldwide, with life-threatening complications if not managed correctly. Previous in vitro studies have utilized change in motility patterns of adult female worms to assess the efficacy of anthelmintics qualitatively. However, it is the third stage larvae (L3) that are infectious to humans. With differential staining using propidium iodide penetration as the indicator of death, we can distinguish between dead and live larvae. This assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…These drugs are the major course of treatment against parasitic nematode infections. The only previous systematic investigation in vitro of anthelmintic drugs on A. cantonensis has been described recently using third-stage larvae ( Jacob et al, 2021 ). However, drugs were tested at a very high concentration (1 mM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These drugs are the major course of treatment against parasitic nematode infections. The only previous systematic investigation in vitro of anthelmintic drugs on A. cantonensis has been described recently using third-stage larvae ( Jacob et al, 2021 ). However, drugs were tested at a very high concentration (1 mM).…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies were done using adult worms. The only previous studies in vitro of anthelmintic agents on A. cantonensis has been described recently against third-stage larvae (L3) at a very high drug concentration ( Jacob et al, 2021 ) but the activity on first-stage larvae (L1) was not assessed. Using the L1 larvae isolated from feces of an A. cantonensis -infected rat, which allows markedly higher throughput than the third-stage larvae and adult worm-based assay, the purpose of this study was to evaluate the antiparasitic activity of the major anthelmintic drugs, including those listed in the WHO Model List of Essential Medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Benzimidazoles are one of the few classes of anthelmintics that are effective against A. cantonensis [ 157 ], especially albendazole, which is currently the only available FDA-approved benzimidazole known to be capable of crossing the BBB [ 11 ]. An increasing number of guidelines recommend the use of albendazole–corticosteroid cotherapy for the management of neuroangiostrongyliasis, for example, the Sydney Children’s Hospital Network, Australia (2018) [ 158 ]; the Children’s Health Queensland Hospital and Health Services, Australia (2019) [ 159 ]; the Hilo Medical Center, Hawaii (2020) [ 160 ]; and the Hawaii Governor’s Joint Task Force on Rat Lungworm Disease Clinical Subcommittee [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of guidelines recommend the use of albendazole–corticosteroid cotherapy for the management of neuroangiostrongyliasis, for example, the Sydney Children’s Hospital Network, Australia (2018) [ 158 ]; the Children’s Health Queensland Hospital and Health Services, Australia (2019) [ 159 ]; the Hilo Medical Center, Hawaii (2020) [ 160 ]; and the Hawaii Governor’s Joint Task Force on Rat Lungworm Disease Clinical Subcommittee [ 9 ]. Experimental studies have also demonstrated the in vitro efficacy of albendazole on A. cantonensis L3 [ 157 , 161 ]. However, doubt remains regarding albendazole’s safety, primarily due to concerns that it may cause further inflammation and associated complications induced by the killed larvae in the brain [ 3 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latest research on infection in non-human species is described (Feckova et al, 2021;Malik et al, 2021;Tsai and Chen, 2021;Wun et al, 2021a, b). Methods for preventing infection or reducing risks of human exposure (Howe et al, 2021;Steel et al, 2021), documentation of chronic sequelae (Meyer, 2021) and updates on research in disease diagnosis and treatment (Ansdell et al, 2021;Eamsobhana et al, 2021;Jacob et al, 2021;Jarvi et al, 2021) are provided. We hope these research papers will provide clinicians, researchers, educators and the general public with information that might help to reduce the risk of infection in humans and other animals, develop more efficient and targeted diagnostic methods, rationalise therapeutic approaches in acute and chronic cases, and direct future research on this fascinating but potentially destructive disease.…”
Section: Long-term Sequelaementioning
confidence: 99%